ETOS KERJA ISLAM DALAM PENDIDIKAN ISLAM - Rifqi Muntaqo; Muhammad Khozinul Huda (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
Ethos as understood as two moral nitai as a unity of goodness of action that is always done or a commendable action done in certain professions. First, the orientation of moral values as the basis of a person's moral attitude in behaving and acting as part of his profession and can be a standard that should or should be followed for others and certain communities of his time. Second, the evidence of practice and the way in which it executes the hat. Therefore, the evidence that moral values form the basis of the moral attitude of this commendable act means one on the plane of thought or concept, and on the other hand lived its implementation in life or in one of its fields. An important work is based on three dimensions of human consciousness, namely; Dimension Makrifat, dimension makrifat based on the ability of a person to be able to understand the signs that Allah has spread as a mercy for his makhluq. Dimensions of Nature, understanding of selfattitude to establish a goal where the direction of action is taken. And Shari'a Dimension, its orientation that action is more imprint than just saying (action speaks louder than a word). Achieve an Islamic work ethic such as having confidence and optimism, free soul feeling, God's confidence is always in my heart, insightful and profound, competitive and positive, authoritative, and most importantly the ability to predict the future well.